Correlation between NT-proBNP and blood pressure variability with cardiovascular events in patients undergoing maintaining hemodialysis - GAO Xiang; SU Hua-jun; DENG Liu-fen; WANG Hui (Linchuang shenzangbing zazhi)
Objective To analyze the correlation between NT-proBNP and blood pressure variability( BPV) with the cardiovascular events in patients undergoing maintaining hemodialysis( MHD).Methods 212 patients with end-stage renal disease combined with hypertension were selected into our study from September 2014 to September 2016. All of them received MHD at least 6 months. Ninety-one patients with cardiovascular events were assigned into the observational group and the rest 121 cases without cardiovascular events served as the controls. Clinical indexes such as age,gender,diabetes,increased rate of body weight between two times of MHD,blood biochemical indicators were analyzed. Results Univariate analyses revealed that the factors impacting the cardiovascular events included the NTproB NP levels,diabetes,increased rate of body weight between two times of MHD and SBP-SD,SBPCV,DBP-SD,DBP-CV during hemodialysis. The multivariate Logistic Regression analysis showed NTproB NP,SBP-SD and DBP-SD were the major risk factors for cardiovascular events. The ROC curve analysis revealed that the optimal cutoff of NT-proBNP,SBP-SD,DBP-SD to predict cardiovascular events was 7. 32 ng/L,21. 60 mmH g,12. 54 mmH g,respectively. Conclusions Many factors influence the cardiovascular events of MHD patients. Among them,NT-proBNP,SBP-SD,DBP-SD during hemodialysis are newly-detected and major risk factors and should be attached importance to,and have a better predictive value in cardiovascular events.